Enhancing individuals’ engagement in marine recreational sport activities: from an institutional perspective - Minghuan Shou; Jiawei Xu (Frontiers in Marine Science)
IntroductionEncouraging consumer participation in marine recreational sport activities is recognized as a key strategy for boosting both local and regional economies. However, compared to other traditional outdoor activities, participation rates in marine recreation remain relatively low. Two major barriers to participation are consumers' concerns about whether marine recreational sport activities are interesting and suitable for themselves, which can be summarized into product quality uncertainty and product fit uncertainty.MethodsTo address this issue, this paper, grounded in institutional theory, investigates how different institutional environments influence consumers' product certainty and their behavioral engagement in marine recreational sport activities—an area previously underexplored in the literature.Results and discussionsBy collecting 292 survey responses and utilizing ordinary least squares (OLS) regression analysis, we found that both product quality certainty and product fit certainty have a significant positive effect on consumers' behavioral engagement. Additionally, both the regulatory-normative and cognitive institutional environments were shown to significantly enhance consumers' product quality and fit certainty. Moreover, age was found to moderate these effects, with a positive influence on the relationship between the regulatory-normative environment and product certainty, while only affecting the relationship between the cognitive institutional environment and product fit certainty.